(untitled) (Journal Of Educational and Psychological Researches, 2022)
The study aims to identify the neurological perfectionism of talented girls with disabilities and do a case study for one of these girls. The sample of the study consisted of (11) female students at the university level, 5 females with disability and (6) normal female-students. The sample also included (19) secondary school female students in Tabuk region, including 10 students with visual disability and (9) normal students. The case study was limited to one case of mentally superior girls (talented) with kinetic disability. The researcher adopted the descriptive methodology (case study), he used neurological perfectionism scale, Salah Mekhemar interview, Stanford interfacial intelligence scale fifth picture, case study form. The results revealed that there are statistically significant differences between the mean grades of disabled and non-disabled talents in the neurological perfection scale with different dimensions and the total score in favor of the handicapped, there is a statistically significant relationship between the IQ of the disabled and the degree of neurotic perfectionism. To verify the validity of this hypothesis, the correlation coefficients between the IQ of the individuals of the sample and the degree of neurotic perfectionism were achieved in all dimensions and the total score. This was proved by verifying the dynamic factors in the case of the clinical study sample.